ETHICS OF FINANCIAL MANAGERS IN THE MANAGEMENT OF ISLAMIC FINANCIAL INSTITUTIONS - Dudang Gojali; Iwan Setiawan; Ah. Fathonih; Mualimin Mochammad Sahid (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
The purpose of this study is to analyze financial managers' ethics in managing Islamic financial institutions. This research uses the description-analytical method and qualitative approach. Sources and data collection techniques use literature studies relevant to the topic being analyzed. Data analysis uses a combination of deductive and inductive approaches. The results showed. The ethics of financial managers in an enterprise seeks to create and maintain the economic value or wealth of the company. As for the functions of financial management, there are three, the first of which regulates capital allocation to the company's assets. Second, make decisions related to the fulfillment of capital needs. Third, managerial decisions or streamlining the funds used. Meeting capital needs is often complicated for companies of the three functions. The role of financial management includes the activity of obtaining funds to finance the business, the activity of managing the funds received so that the company's goals are achieved, and the actions of managing the assets owned by the company effectively and efficiently.